Application of chitosan film as a binding phase in the diffusive gradients in thin films technique (DGT) for measurement of metal ions in aqueous solution - de Faria, Carol C. [UNESP]; Favero, Mariana; Caetano, Marina M. M. [UNESP]; Rosa, Andre H. [UNESP]; Tonello, Paulo S. [UNESP] (Springer Nature, 2020)
Diffusive gradients in thin films technique (DGT) allows in situ determination of labile metal in water, soils, and sediments. This paper aims to evaluate the performance of a new proposal of DGT to measure Cu2+ and Cd2+ in aqueous solution using chitosan films as binding agent. These films were prepared and characterized (Fourier transform infrared spectroscopy, scanning electron microscopy, atomic force microscope, and elemental analysis). The maximum adsorption rates onto chitosan films at initial concentrations of 0.5 and 1.0 mg L−1 for Cu2+ and Cd2+ were 97%, 98% and 60%, 62%, respectively. Effects of main DGT parameters were evaluated and the results obtained suggest that the pH between 4.0 and 6.0 and ionic strength from 0.0008 to 0.1 mol L−1 presented the best ranges for the application of DGT–Chitosan. The results suggest that chitosan films prepared in this work can be an effective binding agent for DGT technique in aqueous solution. [Figure not available: see fulltext.].
Keywords: Alternative binding phase; Bioavailable; Lability; Metal removal